The Equality of Material and Non-Material Culture in Reconstructing Muarajambi Temple as Center of Education - Fitriaty Fitriaty; Asyhadi Mufsi Sadzali; Amir Husni; Ade Octavia (Dinasti International Journal of Education Management And Social Science, 2025)
Archaeological research in various parts of Indonesia has helped the construction of local and national identities as a unifying narrative of the nation. The results of archaeological research on the Srivijaya Kingdoms have been used as a historical basis for building Indonesia's identity as a maritime and agrarian nation spread across the archipelago. Archaeological research has grown rapidly since the 1800s and focuses on material culture such as artifacts and features without seeing other non-material objects around them. This paradigm produces a limited narrative that only views humans as the solo actors in the process of cultural formation in civilization, while non-material objects such as the natural environment have been marginalized from the process of identity reconstruction. This phenomenon raises the question of what approach can accommodate material and non-material culture used in one whole perspective in reconstructing identity. This article is theoretical with a desk study of Witmore's thoughts. From the review, it is known that the symmetrical archaeology approach places material and non-material culture as equal data in interpreting the past which produces a more in-depth narrative with various perspectives. Symmetrical archaeology is also able to see the role of non-material culture such as the environment, and thought as active actors in the process of cultural formation. Symmetrical archaeology bridges the connectivity between identities in comprehensive narrative.